Microbiology of secondary infections in Buruli ulcer lesions; implications for therapeutic interventions - Gyamfi, Elizabeth; Narh, Charles A; Quaye, Charles (BMC Microbiology, 2021)
Background: Buruli ulcer (BU) is a skin disease caused by Mycobacterium ulcerans and is the second most common mycobacterial disease after tuberculosis in Ghana and Côte d’Ivoire. M. ulcerans produces mycolactone, an immunosuppressant macrolide toxin, responsible for the characteristic painless nature of the infection. Secondary infection of ulcers before, during and after treatment has been associated with delayed wound healing and resistance to streptomycin and rifampicin. However, not much is known of the bacteria causing these infections as well as antimicrobial drugs for treating the secondary microorganism. This study sought to identify secondary microbial infections in BU lesions and to determine their levels of antibiotic resistance due to the prolonged antibiotic therapy required for Buruli ulcer. Results: Swabs from fifty-one suspected BU cases were sampled in the Amansie Central District from St. Peters Hospital (Jacobu) and through an active case surveillance. Forty of the samples were M. ulcerans (BU) positive. Secondary bacteria were identified in all sampled lesions (N = 51). The predominant bacteria identified in both BU and Non-BU groups were Staphylococci spp and Bacilli spp. The most diverse secondary bacteria were detected among BU patients who were not yet on antibiotic treatment. Fungal species identified were Candida spp, Penicillium spp and Trichodema spp. Selected secondary bacteria isolates were all susceptible to clarithromycin and amikacin among both BU and Non-BU patients. Majority, however, had high resistance to streptomycin. Conclusions: Microorganisms other than M. ulcerans colonize and proliferate on BU lesions. Secondary microorganisms of BU wounds were mainly Staphylococcus spp, Bacillus spp and Pseudomonas spp. These secondary microorganisms were less predominant in BU patients under treatment compared to those without treatment. The delay in healing that are experienced by some BU patients could be as a result of these bacteria and fungi colonizing and proliferating in BU lesions. Clarithromycin and amikacin are likely suitable drugs for clearance of secondary infection of Buruli ulcer.
Keywords: WACCBIP; Buruli ulcer; Mycobacterium ulcerans; Secondary Infection; Antimicrobial resistance; Antibiotics; Adiza Abbass; Bartholomew Dzudzor; Lydia Mosi